Global challenges and strategic disruptors in Asian businesses and economies - Ordóñez de Pablos, Patricia, 1975-; Lytras, Miltiadis D., 1973- (Advances in business strategy and competitive advantage., 2021)
"The book presents a collection of chapters exploring and discussing the state-of-the-art, emerging topics, challenges and success factors in business, big data, innovation and technology in Asia, exploring how IoT, big data and AI can provide solutions for global challenges and companies"--